High magnification crack-tip field characterisation under biaxial conditions - B. Moreno; P. Lopez-Crespo; J. Zapatero (Fracture and Structural Integrity)
This work presents a novel methodology for characterising fatigue cracks under biaxial conditions. The methodology uses high magnification Digital Image Correlation (DIC) technique for measuring displacement and strain crack-tip fields. By applying micro-speckle pattern on the metal surface it is possible to achieve high magnification for DIC technique. The speckles were created by electro-spray technique. The validity of this novel technique is demonstrated by direct comparison with standard extensometer measurements, under tension-compression and torsion conditions. In order to image the correct region, the notch effect on the fatigue life was also evaluated.